Learning Community Management in Improving Teacher Competence at SDN Bojongkoneng and SDN Bojongkadu, Cianjur Regency - Asep Cipta Permana; R. Supyan Sauri (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study focuses on the critical need to improve teacher competence at SDN Bojongkoneng and SDN Bojongkadu through effective learning community management. The research aims to describe the implementation of learning community management, analyze the resulting improvements in teacher competence, and identify the underlying factors influencing the effectiveness of this management. Utilizing a qualitative approach with a case study design, data were collected through participatory observation, in-depth interviews, and documentation analysis. The theoretical framework integrates social learning theory and teacher professional development theory, grounded in the Indonesian Teacher and Lecturer Law and policies on continuous professional development. The findings indicate that the applied learning community management systematically encompasses the planning, implementation, and evaluation of community activities. The rigorous execution of this management framework has demonstrably improved teacher competence across pedagogical, professional, social, and personal dimensions. Key factors influencing effectiveness include the visionary leadership of the principal, active and sustained teacher participation, and the strategic allocation of resources. The study concludes that highly effective learning community management is a catalyst for the continuous and holistic improvement of teacher competence in elementary education.